-8-2(-8p+10)=10+7p-2

Simple and best practice solution for -8-2(-8p+10)=10+7p-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-2(-8p+10)=10+7p-2 equation:



-8-2(-8p+10)=10+7p-2
We move all terms to the left:
-8-2(-8p+10)-(10+7p-2)=0
We add all the numbers together, and all the variables
-2(-8p+10)-(7p+8)-8=0
We multiply parentheses
16p-(7p+8)-20-8=0
We get rid of parentheses
16p-7p-8-20-8=0
We add all the numbers together, and all the variables
9p-36=0
We move all terms containing p to the left, all other terms to the right
9p=36
p=36/9
p=4

See similar equations:

| −3x2+12x−120=0 | | -10z-10=10-8z | | 7(4x-3)=-217 | | 400-2a=224 | | 6=x-2+10 | | 3(1+7a)=-81 | | -6(-4x+2)=-132 | | 200000=0.2*x | | 4(y–3)=-5y+51 | | 0.602=j-75 | | (5x*5x)+43=(x-1)(5x+6) | | 9x+3(52x)=15(x+1) | | m/42=-26 | | -5(1+5x)=-230 | | 200,000=0.2*x | | 0=12x^2-20x+6 | | 3-2x/4= | | 6=20-2/3x | | Y=25x-50 | | -5(x+6)-18x=-5(x+9)-3 | | 4x+12+90+30=90 | | 12=3(z−76) | | 3-2x/4=x | | -2z-0z=-2(1) | | 7+n/6=1 | | 592=6k | | 5A+12a=37-14 | | 3-4s=-25 | | 0=10+2x-4x^2 | | 3x²+x=10 | | (24)(39)=2x-4(x+6) | | -25=2y+(-15) |

Equations solver categories